2002
DOI: 10.1093/neucas/8.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Widening the Sphere of Influence: Using a Tool to Extend Extrapersonal Visual Space in a Patient with Severe Neglect

Abstract: We report evidence that visual representations of space close to the body can be extended when a patient uses a tool to explore the environment. HB had severe neglect of left and far spatial regions which was determined more by how locations were visually perceived than by how they were represented tactilely or through proprioception. His ability to detect visual targets in left and far space was improved, however, when he held a tool. He also had limited tactile/proprioceptive knowledge about the location of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 0 publications
5
24
0
Order By: Relevance
“…In contrast to studies that have suggested that tool use expands the representation of the participant's limb so that it encompasses the entire tool [10][12] or the end-effector [23], [25], [26], Povinelli et al [27] suggest that separate spatial representations exist for the hand and the tool in peripersonal space. This could explain the absence of a tool effect in the touching trials of our study, because participants would use the appropriate representation to determine the location of the object for each task.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast to studies that have suggested that tool use expands the representation of the participant's limb so that it encompasses the entire tool [10][12] or the end-effector [23], [25], [26], Povinelli et al [27] suggest that separate spatial representations exist for the hand and the tool in peripersonal space. This could explain the absence of a tool effect in the touching trials of our study, because participants would use the appropriate representation to determine the location of the object for each task.…”
Section: Discussionmentioning
confidence: 81%
“…The first one is that distances are judged in relation to affordances such as reachability, so that a tool that expands the range of positions that are reachable stretches the ruler which is used to scale apparent distance, leading to a decrease in the judged distance of the target [9]. Alternatively, tool use might expand the representation of the participant's limb so that it encompasses the tool [10][12]. If the fact that the representation encompasses the tool is ignored in subsequent judgments, then the expanded representation could be considered as an increase in the judged length of the arm (although arm length is not judged as such).…”
Section: Introductionmentioning
confidence: 99%
“…Some patients may manifest a more severe neglect in the case of lines located in near space than with more distant lines (Halligan and Marshall 1991;Berti and Frassinetti 2000), while others manifest the reverse configuration (Coslett et al 1993;Cowey et al 1994;Vuilleumier et al 1998). Indeed, it is especially to note that several other studies have demonstrated that patients showing a more pronounced neglect for near space begin to manifest the same severe deficiencies for far space if they carry out the bisection task along lines situated in the far distance with the help of a stick (Berti & Frassinetti;Pegna et al 2001;Ackroyd et al 2002).…”
mentioning
confidence: 96%
“…1 The opposite dissociation in which hemispatial neglect is evident in far but not near space has also been reported. [4][5][6][7][8] A patient with neglect of near space was shown to demonstrate neglect in far space when actions were made using a long stick. [4][5][6][7][8] A patient with neglect of near space was shown to demonstrate neglect in far space when actions were made using a long stick.…”
mentioning
confidence: 99%
“…[4][5][6][7][8] A patient with neglect of near space was shown to demonstrate neglect in far space when actions were made using a long stick. 8 A conflicting study of a patient with neglect of far right and near left space 6 showed that neglect was reduced when the patient held a ruler that appeared to extend his more intact representation of (near right) space across longer distances. 4 Others have also demonstrated that the use of a tool was also associated with worse neglect.…”
mentioning
confidence: 99%